A digital imaging method for measuring banana ripeness. Issue 5 (14th April 2012) - Ji, Wei; Koutsidis, Georgios; Luo, Ronnier; Hutchings, John; Akhtar, Mahmood; Megias, Francisco; Butterworth, Mick
<x xml:space="preserve">Abstract</x> Visually assessed appearance is undoubtedly of great importance to the selection of fruit by the consumer at the point of sale while the food supply chain also heavily relies on colour assessment methodologies for the determination of product quality. The use of printed colour charts to assess the ripening stages of fruits (i.e., banana ripeness charts) and/or vegetables is common in the fresh produce supply chain, even though they have limitations. However, the development of a more reliable and an objective instrumental method is necessary to describe fruit ripeness using set colour appearance parameters rather than subjective evaluations based on colour charts. In this article, we report a novel digital imaging methodology that could be used by the fresh produce industry to estimate the ripening stages of bananas more accurately. © 2012 Wiley Periodicals, Inc. Col Res Appl, 38, 364–374, 2013